Experimental Investigation on Sandstone Permeability under Plastic Flow: Permeability Evolution Law with Stress Increment - Peng Gong; Xiaoyan Ni; Zhanqing Chen; Yu Wu; Jiangyu Wu (Geofluids)
Permeability is an important physical property of rock. In rock and rock-like materials, permeability after yielding is closely related to plastic flow behavior. Theoretical analysis and experimental investigations are effective and reliable ways of studying the evolution of permeability. In this paper, fluid flow tests of sandstone samples under 11 stress states were conducted using the MTS 816.02 rock mechanics testing system and a self-designed permeation system. A new plastic flow rule was proposed based on the Mohr-Coulomb yield criterion and a nonassociated flow rule. The applicability of the flow rule was verified by comparing the estimated and experimental values of the equivalent shear strain of the Mohr–Coulomb criterion. Two new coefficients were defined to reflect the influence of the volume deformation and shear deformation on the permeability. A permeability model for plastic flow was established, which can be used to calculate both single-step and multistep permeability estimates of the sandstone samples during plastic flow. The errors of both estimation methods were analyzed. The experimental results showed that the plastic multiplier for the sandstone samples was positive during unloading conditions and negative during loading conditions. The experimental value error of the single-step permeability estimation was less than 16.5%. The experimental value errors of the multistep permeability estimations varied between 15.6% and 16.7%, indicating that the iterative format of the multistep permeability estimation method was generally stable and highly precise. A comparison of the permeability influence coefficients indicated that the influence of the equivalent shear strain on the permeability was smaller than that of the volumetric strain.